Analysis of Drainage System Planning in Newtown Park Housing Development Sidoarjo District - Moh Rizqy Hidayanto; F Rooslan Edy Santosa; Ronny Durrotun Nasihien (NAROTAMA UNIVERSITY, Indonesia, 2021)
Some areas in Indonesia often experience flood problems, therefore it is necessary to have an adequate and good drainage system planning so that community activities in an area are not disturbed. The location of this research is located in the newtown park housing development in Damarsih Village, Buduran District, Sidoarjo Regency. with land area ± 72.548 m². Rain station data used were from Bono, Sruni, Sedati, Banjarkemanten in the period 10 years 2009-2019. The direction of discharge of water from the study site was directed at small afv pepe, then continued to afv pepe. With the analysis of HSS Nakayashu at the 25 year return period, the discharge that occurred was not greater than the carrying capacity of Small afv pepe and afv pepe. The maximum discharge that occurs at the research location with the Rational method is 17,404 m3/s, the maximum discharge in the Weduwen method is 27,917 m3/s. Rational Discharge was chosen because the calculation of the length of rain can be known for sure so as to strengthen the level of certainty of the results obtained. For the capacity requirements in the research location with the rational method, the peak discharge for the 5-year return period is 1,858 m3/s and the volume of capacity required during high rain (27 minutes) is 3009 m3 and can be accommodated with a drainage channel of 5217.43 m3 and bozem. with a capacity of 720 m3 which has an area of ??400 m2 with a depth of 1.8 m.